Geodata in science - a review of selected scientific fields - Michal Apollo; Mateusz Jakubiak; Sorin Nistor; Paulina Lewinska; Artur Krawczyk; Lukasz Borowski; Mariusz Specht; Karolina Krzykowska-Piotrowska; Łukasz Marchel; Agnieszka Pęska-Siwik; Miroslav Kardoš; Kamil Maciuk (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Today, completely new forms of geo-information systems are becoming increasingly popular. New technological possibilities allow these systems to be adapted to the requirements and needs of societies. This paper is an extensive literature review of the use of geodata in various scientific fields, in STEM (science, technology, engineering, and mathematics) disciplines. However, as there is no universal agreement as to which disciplines are included in the STEM, the authors also included related fields such as geography or transport.